Ecological aspects of the horned leaf-frog proceratophrys mantiqueira (Odontophrynidae) in an atlantic rainforest area of southeastern Brazil - Almeida-Santos, Marlon; Siqueira, Carla Costa; Anjos, Luciano Alves [UNESP]; van Sluys, Monique; Rocha, Carlos Frederico Duarte (My University, 2017)
This study presents information on habitat use, diet, reproductive aspects of, and the helminth parasite community in, the frog Proceratophrys mantiqueira from an Atlantic Rainforest area (APA Mantiqueira) in southeastern Brazil. Frogs were collected at altitudes between 1200 and 1775 m. The estimated population density of P. mantiqueira in the area was 2.0 ind/100 m2, and the microhabitat most frequently used (82% of the individuals) was the leaf litter on the forest floor. The diet was composed by 20 types of prey items, with Coleoptera and Orthoptera contributing the most important items. The width of the mouth affected the volume of prey consumed by P. mantiqueira, as is expected for frogs, because they swallow their prey whole. There were ontogenetic changes in the types of prey in the diet of P. mantiqueira, with no ingestion of Coleopteran adults by juvenile frogs (< 26 mm). The clutch size of females of P. mantiqueira (692–923 eggs) was similar to those reported for the congeners P. appendiculata and P. tupinamba, but slightly smaller than those recorded for larger species of Proceratophrys such as P. boiei and P. caramaschii. Despite occurring at relatively low densities in the study area, P. mantiqueira had a high prevalence of infection by helminthes (90%), possibly because the helminth parasite community was mostly composed by host-generalists and monoxenous life-cycle species. Diet composition and rates of en-doparasite infection, but not microhabitat use, changed with the age structure of the studied populations of P. mantiqueira.
Keywords: Anura; Body size; Diet; Helminth load; Microhabitat; Reproductive biology